DEVELOPMENT OF LEARNING SPACES WITH TECHNOLOGY MEDIA: LEARNING USING THE WORDWALL WEBSITE AT TK DHARMA WANITA PERSATUAN IN PANDANARUM VILLAGE THROUGH THE WORK PROGRAM OF KKN-P GROUP 38 - Purnomo, Istiqomah (Journal of Social Comunity Services, 2024)
Kindergarten is an important period in a child's development. During this time, children need to get the right stimulation to support their growth and development. One way to provide this stimulation is by providing an interesting and fun learning space. Information and communication technology (ICT) has developed rapidly and become an integral part of everyday life, including in the world of education. This program aims to improve the use of technology media in learning at Dharma Wanita Persatuan Kindergarten in Pandanarum Village, Pacet District, Mojokerto Regency. This program uses the Word Wall website as an interactive and engaging learning platform. This website provides various educational game templates that can be used to increase learner motivation and participation